Middle Powers in Asia and Europe in the 21st Century - Giacomello, Giampiero (Foreign policies of the middle powers., 2020)
This volume argues that middle powers are important to 21st Century world politics in performing roles as (aspiring) global middle powers, regional pivots, and niche leaders. This claim is based on an analysis of the foreign policies of nine (aspiring) middle powers from the Near East, East Asia, and Europe.